Species identification of Late Pleistocene bat bones using collagen fingerprinting. (11th November 2019) - Buckley, Michael; Herman, Jeremy
Abstract: Bats form the second most diverse mammalian order (Chiroptera), after rodents, and vary widely in their physiology and ecology. Those species that live in temperate climates are generally insectivorous and nocturnal or crepuscular, sheltering in tree hollows, caves, or buildings during the day. They are potentially valuable ecological indicators, due to their dependence on suitable roosting sites and arthropod food, both of which are commonly affected by human activities. Identification of bats from ancient assemblages that are found in caves could therefore provide useful data for palaeoenvironmental reconstructions and show the effect of habitat loss. Here, we apply the recently developed approach of collagen fingerprinting by soft ionisation mass spectrometry to the identification of ancient bat remains in an archaeological assemblage from Pin Hole Cave (Derbyshire, England). Our results show that a simple set of markers can distinguish all seven genera of bats known to be present in either modern or ancient Britain ( Myotis, Nyctalus, Pipistrellus, Barbastella, Plecotus, Eptesicus, and Rhinolophus ). Further analysis indicates that species‐level determination is possible in some of these taxa, but it would more readily be achieved using the more advanced methods of collagen sequence analysis by liquid chromatography coupled with tandem mass spectrometry. Within our assemblage yielding 6, 800 ancient bone collagen fingerprints, we identified only 1% that derived from chiropterans, and these were predominantly derived from Myotis (two apparent Brandt's bat fingerprints but the majority indistinguishable between the whiskered, Daubenton's and Natterer's bats), Barbastella (the western barbastelle being the only member of this genus known within Europe), and Rhinolophus (identified as the lesser horsehoe bat R. hipposideros rather than the rare greater horseshoe bat R. ferrumequinum ). We infer that the site was likely used by roosting bats throughout the year, and the accumulation of these remains was probably not the result of predator activity. More importantly, the peptide biomarkers provided here could proove valuable in the more systematic analysis of microfaunal remains across many European archaeological and palaeontological sites, preferably those that are collected with well curated stratigraphical information and chronological frameworks.